Analysis of Patient-reported Outcomes of Quality of Life and Functioning Before and After Treatment of Major Depressive Disorder Comorbid With Alcohol Use Disorders. Issue 1 (January 2017) - Danovitch, Itai; Steiner, Alexander Joseph; Kazdan, Anna; Goldenberg, Matthew; Haglund, Margaret; Mirocha, James; Collison, Katherine; Vanle, Brigitte; Dang, Jonathan; IsHak, Waguih William
Abstract : Objective: Alcohol use disorders (AUDs) are common among persons with major depressive disorder (MDD) and have an adverse impact on course of illness and patient outcomes. The aim of this study was to examine whether AUD adversely impacted patient-centered outcomes in a sample of research subjects evaluated as part of a large clinical trial for depression. The outcomes of interest to this post hoc analysis are quality of life (QOL), functioning, and depressive symptom severity. Methods: We analyzed 2280 adult MDD outpatient research subjects using data from the Sequenced Treatment Alternatives to Relieve Depression trial. We compared entry and post-selective serotonin reuptake inhibitors (SSRI) treatment QOL, functioning, and depressive symptom severity scores between 121comorbid MDD with AUD (MDD + AUD) subjects and 2159 MDD-no-AUD subjects, and also differences between subjects categorized as remitters versus nonremitters within each group at exit. Results: At entry, MDD + AUD subjects reported similar QOL, functioning, and depressive symptom severity compared with the MDD-no-AUD subjects. After treatment with citalopram, both groups showed significant improvements throughout treatment; however, 36% to 55% of subjects still suffered from severely impaired QOL and functioning at exit. Conclusions: The overall study population demonstrated a significant response to treatment with large effect sizes in depressive symptom reduction, but to a lesser extent in QOL and functioning. Findings suggest that subjects with MDD + AUD benefited equally as MDD-no-AUD from treatment with selective serotonin reuptake inhibitors (SSRI) medication, yet both groups continue to experience reduced QOL and functioning after treatment. Monitoring QOL and functioning is critical to determine whether interventions that improve clinical outcomes also impact patient-centered outcomes, and our analysis suggests that there is a pressing need for innovative interventions that effectively improve these outcomes.